A Study to Assess the Prevalence of the Risk Factors of Coronary Artery Diseases among Women in Guwahati, Assam - Rashmi, Sijagurumayum; Thongam, Bijaya; Borgohain, Unmona (International Journal of Nursing Research, 2023)
Aim: The aim of the study was to assess the risk factors for coronary artery disease among women in Guwahati. Materials and Methods: Quantitative research approach was used, and descriptive design was adopted in the study. The samples were collected using purposive sampling technique from 100 women, who were in the age group of 30–65 years, residing in Guwahati, Assam, and who fulfill the inclusion criteria. Semi-structured questionnaire was used to assess the prevalence of risk factors of coronary artery disease and biophysiological measurement to measure the body mass index (BMI) and blood pressure (BP). Results: It was found that 16% of them were having systolic BP more than 140 mm of mercury, 53% do not perform exercise, and only 15% performed yoga. Nearly 57% of them express that they have stress. Nearly 45% of them were having BMI more than 25 kg/m2 . There was a statistically significant association of risk factor (BP) with age only and also a statistically significant association of risk factor (stress) with education and occupation. Finally, there was also a statistically significant association of risk factor (performance of exercise) with demographic characteristics, i.e., age, education, and occupation at 0.05 level of significance. However, there is no association of risk factor (BMI range) with any of the demographic variable. Conclusion: It was concluded that the risk factor for coronary artery disease was common among the women in Assam and since most of the risk factors were modifiable, timely intervention can help in reducing morbidity and mortality due to this disease.